Combined experimental and DFT-TDDFT investigation on anthocyanidins for application in dye-sensitised solar cells. (August 2017) - Sinopoli, Alessandro; Citro, Ilaria; Calogero, Giuseppe; Bartolotta, Antonio
Abstract: The five naturally most abundant anthocyanidins (delphinidin, cyanidin, pelargonidin, malvidin and peonidin) were investigated experimentally and theoretically for dye sensitised solar cell (DSSC) applications. The five dyes were characterised by UV–Vis absorption spectroscopy and cyclic voltammetry, revealing ideal photophysical and electrochemical properties for their final DSSC application. The molecular geometries, electronic structures, vertical transitions and proton affinity of these molecules were investigated with DFT and TDDFT calculations. All of the studied dyes show photo-energy conversion activity, with efficiencies up to η = 1.4% for pelargonidin. The experimental characterisation together with the computational analysis were fundamental tools in order to better understand the obtained photovoltaic performances and after two decades stopping the cyanidin hegemony in the field of natural dyes for DSSC applications. Graphical abstract: Highlights: Combined experimental and computational studies on the five naturally most abundant anthocyanidins have been carried out. The five pigments revealed ideal photophysical and electrochemical properties for their final DSSC application. All of the studied dyes show photo-energy conversion activity, with efficiencies up to η = 1.4%.